Rhanteriopsis baskilensis sp. nov. (Inuleae, Asteraceae), a new species from Turkey - Hamzaoğlu, Ergi̇n; Behçet, Lütfi̇ (Phytotaxa, 2022)
Some interesting Asteraceae specimens were collected from Baskil (Elazığ, Turkey) with palea on its receptaculum, few and flat pappus bristles. After our examination, it was understood that the specimens belonged to Rhanteriopsis, which is a new genus record for Turkey. The specimens are morphologically similar to R. microcephala, which is endemic to Syria, and R. puberula, which is distributed in Iraq and Iran. However, the Turkish specimens differ from these species in its involucral bracts and paleae being narrower, achenes shorter, and pappus bristles 5. In this study, a detailed description of the new species, its morphological comparison with R. microcephala and R. puberula, photographs and some ecological information are given. In addition, an IUCN threat category is proposed for the new species, taking into account the existing and potential threats to its distribution.